The CLEARWATER project: preliminary results from the geophysical survey in Tympaki, Crete, Greece. - Vafidis, A.; Andronikidis, N.; Hamdan, H.; Kritikakis, G.; Economou, N.; Panagopoulos, G.; Soupios, P.; Steiakakis, E.; Manoutsoglou, E. (Bulletin of the Geological Society of Greece, 2013)
One of the most important environmental problems in coastal areas is the salinization of ground water. The groundwater contamination due to seawater intrusion is usually caused by a violation of a delicate hydrogeological balance that exists between freshwater and seawater in coastal aquifers. The development of a methodology for the prediction of the systematic sea water intrusion can contribute to the planning of effective prevention measures in the coastal areas. The geophysical techniques offer a suitable non-invasive method for determining the geometric characteristics of an aquifer and monitoring the saline water intrusion. Among all geophysical techniques, the most successful methods, concerning the detection of salinization in the coastal areas, are the electric resistivity and electromagnetic methods. Seismic methods can also help in providing further geological information for the stratigraphy. In this work, we present the preliminary results from the geoelectrical survey conducted in Tympaki basin (Herakleio, Greece) within the framework of the project “geophysiCaL basEd hydrogeologicAl modeling to pRevent pollution from sea WATER intrusion at coastal areas”